Tecnología y educación de adultos. Cambio metodológico en las matemáticas - Mª Luisa Barrio de la Puente; Margarita Quintanilla Rojo; José Luis Barrio de la Puente (Revista Complutense de Educación, 2007)
The present work analyses and assesses the application of the information and communication technologies (ICTs) in the education of adult people.This application consists of a methodological investigation in the field of mathematics, specifically in Statistics and Geometry, combining the conventional classroom with the computers lab. The obtained results reflect a better performance and a greater positive attitude on the part of the students and of the professors when they face this matter.